2018
DOI: 10.1155/2018/1057539
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy and Safety of Acupuncture for the Treatment of Children with Autism Spectrum Disorder: A Systematic Review and Meta‐Analysis

Abstract: Objectives. We aimed to summarize and critically evaluate the available evidence regarding the efficacy and safety of acupuncture for children with autism spectrum disorder (ASD). Methods. We searched 13 databases for studies published up to December 2016. Randomized controlled trials (RCTs) evaluating the efficacy of acupuncture for children with ASD were included. Outcome measures were the overall scores on scales evaluating the core symptoms of ASD and the scores for each symptom, such as social communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
0
15
0
6
Order By: Relevance
“…Some research suggests that acupuncture could help ASD children to relieve their symptoms [ 24 26 ]. Moreover, meta-analysis results show that acupuncture could help ASD children reduce their Childhood Autism Rating Scale (CARS) and their Autism Behavior Checklist (ABC) score [ 27 ]. Transcutaneous electrical acupoint (TEAS) combines traditional acupuncture therapy with transcutaneous electrical nerve stimulation, which can produce effects similar to acupuncture [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some research suggests that acupuncture could help ASD children to relieve their symptoms [ 24 26 ]. Moreover, meta-analysis results show that acupuncture could help ASD children reduce their Childhood Autism Rating Scale (CARS) and their Autism Behavior Checklist (ABC) score [ 27 ]. Transcutaneous electrical acupoint (TEAS) combines traditional acupuncture therapy with transcutaneous electrical nerve stimulation, which can produce effects similar to acupuncture [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] As a major form of Chinese medicine, from clinical trials and SRs, acupuncture is reported to improve various developmental and behavioral aspects of children with ASD, it's safe but children experienced pain and cried during the treatment. [ 23 26 ] Tetrahydrobiopterin is an important cofactor in the biosynthesis of catecholamines and serotonin, and in the treatment of ASD, it is reported to significantly improve social interaction subscale of the CARS. [ 27 ] l -Carnosine is a dipeptide known for its antioxidant properties and proposed enhancement of γ-aminobutyric acid function in the brain, with possible anticonvulsive effects, it was showed to significantly improve CARS score on ASD children.…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the possibilities of complementary and alternative therapy in the treatment of ASD, the most promising are considered such interventions, as musical therapy [60-62], sensory-integration therapy, or sensory enrichment of the environment [63], acupuncture [64] and massage [65]. A technology is proposed to enhance physical activity in children with ASD, aimed at developing increased physiological responses to dynamic movements by continuously measuring energy expenditure and heart rate during specially organized training [66].…”
Section: Traditional Approaches To the Treatment Of Autism Spectrum Dmentioning
confidence: 99%